Economic burden to commercial payers of young adults with schizophrenia in Colorado. (1st January 2021) - Pesa, Jacqueline; Patel, Charmi; Rotter, David; Papademetriou, Eros; Potluri, Ravi; Benson, Carmela
Abstract: Aims: The primary objective was to examine direct costs and health resource utilization (HRU) among commercially insured young adults with schizophrenia (SCZ) in Colorado. Materials and methods: The Colorado All-Payer Claims Database, covering approximately 76% of the insured Colorado population was used. Members aged 18–34, with and without SCZ, having commercial insurance were included. All-cause, mental health (MH) related and non-MH related per patient per month (PPPM) costs and per hundred patients per month (PHPPM) HRU were compared between an SCZ cohort and a propensity score matched non-SCZ cohort before and after index date up to 48 months. Results: Five hundred and one patients with SCZ and 2, 510 matched individuals without SCZ were included. HRU and costs were higher for SCZ patients both pre- and post-index date. Pre-index, there were 32.3 (24.0 MH; 8.4 non-MH) PHPPM more office visits; 2.1 (2.7 MH) PHPPM more admissions; 104.8 (67.02 MH; 37.7 non-MH) PHPPM more prescriptions in the SCZ cohort (all p <.01). After index date, the SCZ cohort had 89.6 (81.3 MH; 9.2 non-MH) more PHPPM office visits, 7.2 (6.1 MH; 0.9 non-MH) PHPPM more admissions, and 181.6 (123.1 MH; 58.6 non-MH) PHPPM more prescriptions (all p <.001). All-cause costs in the pre-index period were 457 PPPM (373 MH) higher for the SCZ cohort ( p <.001). In the post-index period, all-cause costs for the SCZ cohort were 1, 687 PPPM (1, 258 MH; 412 non-MH) higher (all p <.001). Approximately, 40% of patients with SCZ were on commercial insurance after four years compared with approximately 75% in the non-SCZ cohort. Limitations: This study was based on data from a single state, thus may not be generalizable to other states. Conclusions: Healthcare costs and HRU for young adults diagnosed with SCZ are significantly more burdensome to commercial payers than matched patients without SCZ, both before and after an official SCZ diagnosis.